Stress and cancer-related lifestyle factors among African American heterosexual couples - Cho, Dalnim (PLoS One, 2020)
Intimate partners can have a profound influence on individuals’ health behaviors. In this exploratory research, we investigated the concordance of cancer-related lifestyle factors including smoking, body mass index, physical activity, fruit and vegetable intake, red meat intake, and alcohol use within African American heterosexual couples. We also examined whether females’ stress is associated with their own (actor effect) and males’ cancer-related lifestyle factors (partner effect), and vice versa. We analyzed a total of 216 heterosexual couples (i.e., N = 432 individuals) recruited from black churches. Intraclass correlation coefficients (ICCs) were calculated and multilevel modeling in which individuals are nested within couples was conducted. Results showed that there was high concordance of body mass index (ICC = 1.68, p < .001), fruit and vegetable intake (ICC = 1.62, p < .001), red meat intake (ICC = 1.50, p = .001), and alcohol use (ICC = 1.74, p < .001) between spouses. A multilevel analysis showed that there were actor and partner effects of stress on females’ BMI; females’ stress was positively associated with their own BMI (actor effect; β = .42, p = .006) and males’ stress was positively associated with females’ BMI (partner effect; β = .39, p = .026). Also, females’ stress was positively associated with their own red meat intake (actor effect; β = .20, p = .019). In conclusion, high concordance of cancer-related lifestyle factors (BMI, fruit and vegetable intake, red meat intake and alcohol use) exists between African American spouses. Given the identified actor and partner effects of stress on females’ BMI, a couple-based lifestyle or weight management intervention that targets both male and female spouses’ stress and coping will be promising, particularly to enhance African American women’s health behaviors. Future studies need to investigate mechanisms underlying concordance and discordance of cancer-related lifestyle factors in African American couples. Also, factors that explain African American male spouses’ health behaviors need to be uncovered.